PEMAJAKAN EKONOMI DIGITAL: KOMPARASI REGULASI INDONESIA, P3B, DAN OECD PILLAR ONE - Fikri Ramadhan; Poppy Rahayu; Indra Pahala (JITAA : Journal Of International Taxation, Accounting And Auditing, 2026)
This study examines the normative conflict between Indonesia’s Significant Economic Presence (SEP) regime and the Permanent Establishment (PE) provisions contained in Double Taxation Avoidance Agreements (DTAAs), while also evaluating the OECD Pillar One framework as a multilateral solution. The research employs a normative legal method with a comparative approach to analyze Indonesia’s SEP regulations, the PE concept under DTAAs, and the OECD Pillar One framework. Data were collected through a literature review and analyzed qualitatively. The findings indicate that SEP possesses strong economic legitimacy in safeguarding Indonesia’s tax base from cross-border digital economic activities. However, its implementation faces legal challenges due to the potential risk of treaty override against DTAA provisions that still require physical presence through the PE concept. Meanwhile, OECD Pillar One offers greater legal certainty through a multilateral mechanism, but its high revenue thresholds may limit its benefits for developing countries. Therefore, Indonesia should maintain SEP as a strategic policy instrument while supporting a more inclusive and equitable global tax reform framework.